Inflation targeting and inflation deviation inertia: A study for Brazil based on the fractional integration approach - Ricardo Ramalhete Moreira; Edson Zambon Monte; André Abdala (Journal of Applied Economics, 2018)
We applied the fractional integration approach to measure inflation deviation inertia in an emerging economy under an inflation targeting regime, as well as to control for potential determinants of such a deviation. We did not base our analysis on typical unit root tests, as we identified a long-memory behavior in inflation deviation. Such a non-conventional procedure can be regarded as a contribution to the inflation targeting literature. From ARFIMA and ARFIMAX estimates, we identified that inflation deviation was mainly determined by a strong inertia degree (AR(1)), commodity prices, nominal exchange rate and economic activity over the entire sample. Moreover, we found an increase of the inflation deviation inertia over the last years of our time sample, thereby indicating a deterioration of the inflation targeting regime in such a specific period.
Keywords: 330; emerging economy; Fractional integration; inflation deviation; long-memory